External antenna design for GPS signal reception enhancement - Abba, I.; Thelaha, Masri; Wan Azlan, Wan Zainal Abidin; Kismet, Hong Ping; Bong, V. P.; Hussaini, N. B.; Mardina, Abdullah (IEEE Computer Society, 2015)
The working paper explains the detailed analysis of the low-cost design and implementation of 53.0 × 41.0 mm Single Microstrip Patch Antenna (SMPA) for handheld Global Positioning System (GPS) receiver external use. A Computer Simulation Technology (CST) microwave studio technique was applied, using the dielectric of 5.0 and substrate thickness of 1.6 mm. The SMPA designed for data acquisition application operating on a single frequency on 1.57542 GHz. The antenna gain enhancement and the signal reception have improved the receiver line-of-sight (LOS) for an indoors experimental usage. However, the external antenna gain overcomes raw data quality degradation caused by the internal antenna due to low elevation angle and results in non LOS